Pengaruh Religiusitas, Kepercayaan, Dan Logo Halal Terhadap Keputusan Pembelian Produk Halal: (Studi Pada Konsumen Sudirman Street food di Kota Bandung) - Widana, Indah Ayu Puji; Artadita, Sherly (eProceedings of Management, 2024)
Muslims are expected to consume halal food and according to Islamic law guidelines, religiosity and trust arevalues and attitudes that can influence human behavior in consuming products, and trust in a product will arisefrom the presence of a halal logo. But in fact at Sudirman streetfood Bandung, some food stands do not yet have ahalal logo and there is no separation of areas between halal and non-halal food stands, which has an impact on thedoubts of some potential consumers in making purchasing decisions. The purpose of this study was to determine theeffect of religiosity, trust and halal logos on purchasing decisions for halal products. The research method appliedis quantitative descriptive approach, nonprobability sampling technique with purposive sampling type with a total of100 respondents with consumers who have visited / bought products at Sudirman street food in Bandung City as thepopulation. The analysis technique used is multiple linear regression analysis using SPSS software version 27.Based on the research results, simultaneously (F-test) and partially (T-test), religiosity, trust and Halal Logo havean effect on purchasing decision. Based on the coefficient of determination, it is found that religiosity, trust andhalal logos on purchasing decisions for Sudirman street food consumers in Bandung City are 42.1% while theremaining 57.9% gets the influence of the halal logo.Keywords-religiosity, trust, halal logo, purchase decision.